Exploratory Factor Analysis Dan Confirmatory Factor Analysis Job Reward With Structural Equation Model - Muhammad Risal Tawil; Mattalatta Mattalatta; Baharuddin Baharuddin; Akmal Umar (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
This study discusses how the measuring instruments of job rewards are adapted and developed through exploratory factor analysis and confirmatory factor analysis using the SPSS analysis tool and the Amos Structural Equation Model (SEM), statistical tools from IBM. This study is intended to establish the dimensions and indicators of job rewards developed with exploratory factor analysis. Furthermore, confirmatory factor analysis is carried out to test the validity and reliability of the job reward indicator to meet the required statistical values. In addition, this study also conducted a model test to obtain a fit model on the job reward construct. This study is a quantitative research that utilizes the survey method using a digital questionnaire instrument created through google forms and distributed for 2 (two) months. The study sample was lecturers at private universities in Baubau City as many as 257 people. The results showed that the 5 dimensions and 25 indicators' job reward construct had high validity and reliability and met the cut-off of the required statistical values. In addition, the indexes of the results of the model tests carried out are declared to have met the criteria of a good model.